Morphological adaptations of signal grass in response to liming and cutting severities - Pereira, Lilian; Passos, Bruna; Herling, Valdo; Luz, Pedro Henrique; Avanzi, Junior (Revista Ciência Agronômica, 2018)
Changes in morphological composition and in the plant population were evaluated during late spring, summer and autumn, in swards of Brachiaria decumbens cv. Basilisk in response to liming (C0.0, without liming; C0.7, limestone amount equivalent to 0.7 ton ha-1; and C1.0, limestone amount equivalent to 1.0 ton ha-1), which were subjected to severe or lenient cutting (40 or 60% of the pre-cutting height, respectively). Increased limestone doses did not result in higher herbage mass (HM), leaf area index (LAI) or proportion of leaves (%L) in the pre-harvest. However, lower proportion of dead material was registered in C0.7 treatment. The treatments C0.0 e C0.7 had higher %L during late spring and summer when associated to severe cutting regimes (R40%), although they reached the pre-harvest condition with lower HM and longer regrowth periods compared to lenient cuttings. The Brachiaria decumbens cv. Basilisk modifies its shoot architecture during the growth season, indicating that lower pre-harvest heights are required during autumn. The absence of liming led to a sharp decreasing of base saturation and levels of K, Ca and Mg in the soil. The minimum annual amount of limestone required for B. decumbens correspond to 0.7 ton ha-1.